Volume 4: Fluid-Structure Interaction 2011
DOI: 10.1115/pvp2011-57451
|View full text |Cite
|
Sign up to set email alerts
|

Main Steam Line Constant Spring Support Failures

Abstract: Several constant spring supports attached to the main steam lines (MSLs) at Palo Verde Nuclear Generating Station (PVNGS) failed over a period of several years. The continued failures presented a need to instrument the MSL piping and supports, such that data could be collected in support of a cause determination and problem resolution effort. Extensive monitoring and data acquisition was performed over an 18-month period in all three PVNGS operating units, encompassing several revisions to the instrumentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Through multiple analyses of the root causes of abnormal pipe expansion and extensive testing of constant force spring hanger performance, it has been found that constant force spring hangers under long-term operating conditions generally experience problems such as large load deviations and excessive load constancy, leading to abnormal pipe expansion and sinking, which significantly impact the safe and stable operation of pipelines [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Through multiple analyses of the root causes of abnormal pipe expansion and extensive testing of constant force spring hanger performance, it has been found that constant force spring hangers under long-term operating conditions generally experience problems such as large load deviations and excessive load constancy, leading to abnormal pipe expansion and sinking, which significantly impact the safe and stable operation of pipelines [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%